Improved element-particle coupling strategy with δ-SPH and particle shifting for modeling sloshing with rigid or deformable structures. (September 2021) - Zhang, Z.L.; Khalid, M.S.U.; Long, T.; Liu, M.B.; Shu, C.
Abstract: Liquid sloshing flows interacting with deformable structures are difficult to be numerically simulated due to the co-existence of moving fluid-structure interfaces and breaking free surfaces. As a Lagrangian and particle-based method, the smoothed particle hydrodynamics (SPH) method has natural advantages in handling free-surface flows. The smoothed finite element method (SFEM) provides a reliable tool to capture the associated structural deformations, and it can solve the "overly-stiff" problem in the conventional FEM. In this work, the coupling strategy of an improved SPH version and SFEM is integrated with advanced fluid modeling techniques, and is extended and validated for modeling liquid sloshing with rigid or deformable structures. Both the rigid wall boundaries and deformable structures are reproduced by the elements, whereas the fluid particles with a different resolution can be adopted. The integrated δ -SPH model can significantly alleviate the spurious high-frequency noise of the computed impact pressure in a sloshing process. The particle shifting technique helps improve both accuracy and robustness of the fluid flow model. The virtual particle coupling strategy is effective to transfer information between SPH particles and SFEM elements. Various numerical tests show that the present coupling approach is very effective for modeling violent sloshing with deformable baffles or deformable container walls. This method is more accurate than the conventional coupling of SPH-FEM and can obtain results very close to the experimental observations compared with some numerical approaches from other sources.